INCREASING THE QUALITY OF LEARNING AND SERVICES EARLY CHILDHOOD EDUCATION IN TULEHU VILLAGE, SALAHUTU SUBDISTRICT, CENTRAL MALUKU DISTRICT, MALUKU PROVINCE - hamid patilima; Maya Nurfadhillah; Nurhidayati Udjir; Rohana; sunarti sulistyowati; Susiana (International Conferences on Early Childhood Education Proceedings, 2023)
In 2021, the government will carry out an education quality mapping activity as a step to collect data and information on the achievements and non-achievement of National Education Standards (NES) indicators. One of the purposes of this quality mapping is to assist educational units in dealing with accreditation. Accreditation is a benchmark for assessing the quality and quality of an institution. Bearing in mind the results of the 2000 Dakkar Declaration on education for all (EFA), all UNESCO members designed priority programs where one of them was a program to improve the quality of education (Indonesian National Commission for UNESCO, nd). Early childhood education is an education that must be prepared in a planned and holistic, integrative manner. So that during development period, children get complete and correct stimulation in accordance with the potential possessed by children (Makleat et al., 2021). This research is classified as a qualitative descriptive research, namely a research process and understanding based on a methodology that investigates social phenomena and human problems. One of the challenges during this research was that there were still many RA/kindergarten institutions that had not been accredited and the unavailability of administration 8 complete educational standards at RA/kindergarten institutions. The purpose of this research is to be able to find out how to improve the quality of learning in early childhood Education (PAUD) and improve early childhood Education services in Tulehu Village, Salahutu subdistrict, Central Maluku District, Maluku Province.